NOUN COMPOUNDS IN THE GERMAN LANGUAGE VERBALIZING THE NEW REALITY DURING THE COVID-19 PANDEMIC - Gulshad Makhdadovna Usmanova (International Journal of Literature and Language Studies, 2026)
The article analyzes the most productive methods of forming noun compounds in the lexical system of contemporary German. The research material consists of compound nouns presented in the electronic dictionary Neologismen – Neuer Wortschatz rund um die Coronapandemie (“Neologisms – New Vocabulary Related to the Coronavirus Pandemic”), compiled by the Leibniz Institute for the German Language in Mannheim. The study aims to identify the specific features of the derivation of compound nouns that verbalize the new reality created by the COVID-19 pandemic, as well as to determine the main word-formation models and evaluate their productivity. The findings demonstrate that compounding remains the most productive means of lexical enrichment in modern German. The most frequent word-formation patterns include compounds without linking elements, compounds with linking elements, prefixal formations, hybrid compounds, and blended words. The analysis also reveals significant tendencies in the development of pandemic-related vocabulary, including synonymic variation, evaluative connotations, extensive borrowing from English, semantic derivation, and the high derivational potential of the lexical bases Corona and COVID.